Identification of Teaching Materials for Physics Edupark City Park Cindua Mato Batusangkar Using Concepts Fitting Technique - Sari, Gina Alya; Rifai, Hamdi; Fauzi, Ahmad; Yumna, Hayyu (PILLAR OF PHYSICS EDUCATION, 2025)
City Park Cindua Mato is a green open space located in the center of Batusangkar city and serves as a place for recreation, sports, and social interaction. The existence of facilities such as basketball courts and reflection stone rides make this park an environment rich in phenomena that can be studied scientifically. Despite having the potential of an environment rich in physical phenomena, its utilization in the context of education is still very limited. Problems found based on direct observation show that students often have difficulty in understanding physics concepts because the teaching materials used tend to be theoretical. Observations also show a lack of learner involvement in learning because the media used has not been able to attract their attention, especially those with visual learning styles. In addition, the teacher said that the current teaching materials have not utilized local potential as a source of learning, so students feel that the material presented is less relevant to their daily lives. This research aims to identify the needs of teaching materials that are in accordance with the characteristics of students and the surrounding environment. This research is a preliminary study of the research and development method with the EDUPARK model, which at this stage is focused on the EDU stage. Data were collected through interviews with 3 physics teachers and distributing questionnaires to 31 students of Class XI Phase F Moving Physics 1 SMAN 1 Sungai Tarab. The results of the analysis show that the available teaching materials have not accommodated the local potential and learning styles of students optimally. Therefore, a teaching material is needed in the form of a physics enrichment book integrated with City Park Cindua Mato Batusangkar that is in accordance with the characteristics of students and their learning environment.